Corporate transactions in hard-to-value stocks - Ben-David, Itzhak,Kim, Byungwook,Moussawi, Hala,Roulstone, Darren (The Ohio State University, Fisher College of Business, Charles A. Dice Center for Research in Financial Economics, 2021)
Hard-to-value stocks provide opportunities for managers to exploit their informational advantage through trading on their firms' and their own personal accounts. In contrast to the prediction that such transactions reflect private information about future events, they are contrarian and heavily depend on past returns. Corporate transactions in hard-to-value stocks outperform those in easy-to-value stocks in the early part of our sample, but this difference disappears after 2002, coinciding with a general decline in the profitability of stock market anomalies. Our evidence is consistent with managers' perception of mispricing, rather than private information, being a key motivator of their transactions
Keywords: Graue Literatur; insiders; repurchases; seasoned equity offerings; private information; mispricing